Fabric battery applicable to high vacuum and wide temperature range and continuous preparation method
Through in-situ construction, interface matching and layer-by-layer composite processes, fabric batteries with high vacuum and wide temperature ranges are prepared, which solves the shortcomings of existing flexible batteries in terms of durability and environmental adaptability, and realizes the water, vacuum and wide temperature range effects of fabric batteries, providing a safer, longer life and environmentally friendly energy supply solution for wearable devices and other flexible electronic devices.
Patent Information
- Application Number
- CN202510045928.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-12
- Publication Date
- 2025-04-15
AI Technical Summary
Existing flexible batteries have shortcomings in high vacuum, wide temperature range and durability, making them difficult to meet the needs of wearable devices and other flexible electronic devices.
Through in-situ construction, interface matching and layer-by-layer composite processes, fabric batteries suitable for high vacuum and wide temperature ranges were prepared. The process includes directly forming an active material layer on the current collector, selecting an appropriate diaphragm for spiral winding, and finally wrapping it with a polymer solution to form an outer protective structure.
It realizes the stress enhancement and solution to the surface shear deformation problems of fiber electrodes, and has the characteristics of water resistance, vacuum resistance and wide temperature range operation. It is suitable for commercial applications and has broad application prospects.
Smart Images

Figure CN119833725A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of flexible batteries and provides a high vacuum, wide temperature range applicable fabric battery and a continuous preparation method. Background Art
[0002] In the digital age, flexible electronic devices are booming in the military and civilian fields, and the market demand for flexible devices such as wearable smart electronic devices and electronic skin is increasing day by day. Traditional rigid structure batteries are not conducive to the construction of flexible devices, so the development of smart electronic devices is subject to certain restrictions. Therefore, designing lightweight, comfortable, portable, and high-energy-density batteries has become a key technology for the research and development of future energy supply equipment. From the perspective of the application of the next generation of smart consumer electronic products, batteries need to achieve stable power output even under various deformations.
[0003] Currently, lithium-ion batteries have the advantages of high energy density, light weight, no memory effect, and low self-discharge rate, making them widely used in many electronic devices. However, lithium-ion batteries have safety hazards in wearable devices, such as overheating and short circuits. At the same time, they take a long time to charge, their lifespan may decrease over time, and their production and processing have a negative impact on the environment. Therefore, a safer, longer-lasting and environmentally friendly alternative is needed.
[0004] Zinc-ion batteries have the advantages of low cost, high safety, high energy density and long cycle life. They are suitable for use in wearable devices and other fields, providing a reliable option for long-lasting and safe energy supply. However, traditional zinc-ion batteries are usually rigid and cannot be bent, making it difficult to achieve high integration and customized use. This has created rigid limitations for many wearable electronic instruments such as wearable medical devices, health monitoring, sports diagnosis, flexible screens, etc., and cannot meet the needs of their actual use. Although some flexible batteries have been studied and reported, their electrical performance, stability and durability are often not comparable to traditional hard batteries. In addition, current fiber battery research is mostly at the small laboratory stage, and it is still impossible to achieve continuous and efficient construction of devices, and it is difficult to achieve normal operation under high vacuum or extreme temperature conditions. In contrast, this work proposes a method for continuously constructing fiber-shaped zinc-ion battery devices, realizing a textile power supply device that can work normally under conditions of immersion in water, high vacuum or wide temperature range (high or low temperature environment), providing a better solution. Summary of the invention
[0005] The present invention aims to solve the technical problems in the field of flexible batteries, and provides a high vacuum, wide temperature range applicable fabric battery and a continuous preparation method thereof. The battery achieves the solution of the stress resistance enhancement and surface shear deformation problems of the fiber electrode through in-situ construction, interface matching and layer-by-layer composite processes, and has the characteristics of water resistance, vacuum resistance and wide temperature range operation, which is suitable for commercial applications and has broad application prospects.
[0006] To achieve the above purpose, the present invention provides the following technical solutions:
[0007] The present invention provides a high vacuum, wide temperature range applicable fabric battery, which is sequentially composed of a positive electrode composed of a current collector loaded with positive electrode active material, a diaphragm layer, a negative electrode composed of a fiber negative electrode, and a surface packaging.
[0008] The positive electrode active material is one of manganese dioxide, vanadium oxide or manganate or a mixture thereof, the proportion of the mixture is in the range of 70%-95%, the proportion of the adhesive is in the range of 1%-10%, and the proportion of the conductive agent is in the range of 1%-20%.
[0009] In the above technical solution, the fiber negative electrode components include Zn or Zn-Cu alloy or a mixture of 70%-100%; adhesive 10%-0%; conductive agent 20%-0%.
[0010] In the above technical solution, the current collector is a carbon-based or metal-based composite with a diameter of 20 μm-
[0011] 500μm;
[0012] The carbon-based material includes one or more of Mxene fiber, graphene fiber, and carbon fiber;
[0013] The metal base includes one or more of copper wire, stainless steel wire, aluminum wire and titanium wire;
[0014] The conductive agent includes one or more of acetylene black, carbon nanotubes, Super P, and graphite.
[0015] In the above technical solution, the surface packaging is a winding wrapping film, and the material of the film includes polyvinyl alcohol PVA, polyvinyl butyral PVB, polyvinyl chloride PVC, polyethylene PE and polyvinylidene chloride PVDC.
[0016] The present invention provides a continuous preparation method of a high vacuum, wide temperature range applicable fabric battery, comprising the following steps:
[0017] In-situ construction:
[0018] The positive or negative electrode active material slurry is evenly coated on the current collector, then dried and solidified in an oven, and collected after roller pressing;
[0019] In-situ construction refers to the formation of an active material layer directly on the current collector, rather than preparing the active material first and then transferring it. Through the process of coating, drying and rolling, the positive or negative active material directly forms a stable layered structure on the current collector.
[0020] Interface matching:
[0021] A separator is selected and spirally wound on an electrode loaded with active materials; the electrode wound with the separator is spirally wound with another fiber electrode to form a battery cell;
[0022] Interface matching emphasizes the close combination and matching between different components. Here, the spiral winding between the separator and the electrode ensures close contact and good electrochemical performance between them. At the same time, the spiral winding between the electrodes also achieves effective matching and connection between them.
[0023] Layer by layer compounding:
[0024] After the battery cell is completely soaked with electrolyte, it is wrapped with polymer solution and dried in an oven to complete the preparation of the fiber battery.
[0025] Layer-by-layer compounding refers to building a battery structure by adding and compounding different materials layer by layer. Here, the battery cell is first infiltrated with electrolyte to ensure that the ion transmission channel inside the battery cell is unobstructed. Then, the battery cell is wrapped with a polymer solution to form an outer protective structure. Finally, the polymer is solidified through a drying process to complete the preparation of the fiber battery.
[0026] Preferably, by mass percentage, the positive electrode layer material components include: 70%-95% of one or a mixture of manganese dioxide, vanadium oxide, manganate, etc.; 10%-1% of a binder; 20%-1% of a conductive agent; the negative electrode layer components include: 70%-100% of one or a mixture of Zn or Zn-Cu alloy, etc.; 10%-0% of a binder; 20%-0% of a conductive agent;
[0027] Preferably, the current collector is a composite current collector on a carbon base such as Mxene fiber, graphene fiber, carbon fiber, etc., or a metal base such as copper wire, stainless steel wire, aluminum wire, titanium wire, etc., with a diameter of 20μm-500μm. The conductive agent is one or more of acetylene black, carbon nanotubes, Super P, and graphite. The adhesive is polytetrafluoroethylene, polyvinylidene fluoride, styrene-butadiene rubber, acrylonitrile multipolymer, etc.;
[0028] Preferably, the viscosity of the positive electrode active material slurry should be controlled at 2000mPa·s-15000mPa·s; the speed of coating the slurry on the current collector is 3cm / min-360cm / min, and the drying temperature is 50℃-220℃; the active material loading density of the obtained electrode is 30mg / m-680mg / m.
[0029] Preferably, the diaphragm is one or more of PP, PE, cable paper, cellulose diaphragm, and non-porous diaphragm; the winding angle between the diaphragm and the positive electrode layer of the fiber battery is 10°-170°, and the winding speed is 5r / min-300r / min. The surface encapsulation is a film wrapped with polyvinyl alcohol PVA, polyvinyl butyral PVB, polyvinyl chloride PVC, polyethylene PE, and polyvinylidene chloride PVDC. It is obtained by dissolving one or more polymer powders in a certain proportion in one or more solvents such as acetone, dimethyl sulfoxide, dimethylformamide, ethanol, etc. and stirring them thoroughly.
[0030] Preferably, the diameter of the fiber negative electrode is 0.02 mm-0.5 mm, the winding angle between the negative electrode or the separator and the positive electrode is 10°-170°, and the winding speed is 5 r / min-300 r / min.
[0031] Because the present invention adopts the above technical solution, it has the following beneficial effects:
[0032] 1. Compared with the prior art, the fibrous zinc ion battery according to the embodiment of the present invention can be continuously constructed into fiber batteries and fabric batteries under air atmosphere, and the raw materials are cheap and easy to obtain, the raw material processing process is simple and energy-saving, the device assembly process is simple, suitable for commercial applications, low production equipment cost, broad application prospects, and can work normally in water immersion, high vacuum and wide temperature range (high or low temperature conditions).
[0033] 2. The present invention overcomes the defects of fiber electrodes constructed by prior art, such as poor stress resistance and inability to withstand the stretching and extrusion of commercial looms. Through in-situ construction, interface matching and layer-by-layer composite preparation methods, the technical problems of weak stress resistance of fiber electrodes, breakage due to surface shear deformation, and difficulty in preparing fabric power sources are solved. At the same time, the effects of constructing fabric devices that are water-resistant, vacuum-resistant and able to adapt to a wide temperature range are achieved.
[0034] 3. The present invention can continuously construct fibrous zinc ion batteries and fabric batteries thereof, which still have a capacity retention rate of more than 50% after 100 cycles, and can still work normally under extreme conditions such as multiple bending, soaking in water, high temperature, low temperature, negative pressure, etc. The raw materials are cheap and easy to obtain, and the raw material processing and device construction processes are simple, which is convenient for commercial application and has broad prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 This is an optical photograph of the 300 m long fibrous zinc ion battery prepared in Example 1 of the present invention.
[0036] Figure 2 This is a microscopic photograph of the cross section of the fiber-shaped zinc ion battery prepared in Example 1 of the present invention. From the figure, it can be seen that the appearance, internal structure and size of the fiber battery are only 1 mm in diameter.
[0037] Figure 3 This is an optical photograph of an energy storage fabric device (20 m*20 m) woven with a fibrous zinc ion battery prepared in Example 3 of the present invention, showing a timer function at -30°C. It can be seen from the figure that the energy storage fabric device has the ability to work at low temperatures.
[0038] Figure 4 This is an optical photograph of an energy storage fabric device (20 m*20 m) woven with a fibrous zinc ion battery prepared in Example 3 of the present invention, with a timer function under the conditions of 80°C and -0.08 mPa. It can be seen from the figure that the energy storage fabric has the ability to work in high temperature or vacuum environment. DETAILED DESCRIPTION
[0039] The following is a detailed description of the embodiments of the present invention. Although the present invention will be described and illustrated in conjunction with some specific embodiments, it should be noted that the present invention is not limited to these embodiments. On the contrary, modifications or equivalent substitutions made to the present invention should all be included in the scope of the claims of the present invention.
[0040] In addition, in order to better illustrate the present invention, numerous specific details are given in the following specific embodiments. It will be understood by those skilled in the art that the present invention can also be implemented without these specific details.
[0041] The present invention solves the technical problems of weak stress resistance of fiber electrodes, breakage due to surface shear deformation, and difficulty in preparing fabric power sources through in-situ construction, interface matching, and layer-by-layer composite preparation methods, while also achieving the effects of constructing fabric devices that are water-resistant, vacuum-resistant, and adaptable to a wide temperature range.
[0042] The principle and mechanism analysis of the present invention to solve the technical problems of fiber electrodes by means of in-situ construction, interface matching and layer-by-layer composite preparation:
[0043] In-situ construction:
[0044] Process: Directly coat the positive or negative electrode active material slurry on the current collector, dry and solidify it in an oven, and collect it after roller pressing.
[0045] Function: This in-situ construction method ensures the close integration of the active material layer and the current collector, avoids damage during the transfer process, and enhances the mechanical strength and stability of the electrode.
[0046] Effect: The stress resistance of the fiber electrode is improved and the fracture problem caused by surface shear deformation is reduced.
[0047] Interface matching:
[0048] Process: Select a separator and spirally wind it on the electrode loaded with active material, then spirally wind the separator-wrapped electrode with another fiber electrode to form a battery cell.
[0049] Function: The spiral winding between the diaphragm and the electrode ensures close contact and good electrochemical performance between them, while the spiral winding between the electrodes realizes effective matching and connection between them.
[0050] Effect: The bonding force between electrodes is enhanced, the overall stability and durability of electrodes are improved, and it is beneficial to the preparation of textile power sources.
[0051] Layer by layer compounding:
[0052] Process: After the battery cell is completely soaked with electrolyte, it is wrapped with polymer solution and dried in an oven to complete the preparation of the fiber battery.
[0053] Function: By adding and compounding different materials layer by layer, a stable battery structure is constructed. The electrolyte infiltration ensures the smooth ion transmission channel inside the battery cell, and the polymer solution wraps around to form an outer protective structure.
[0054] Effect: The fabric device is endowed with the ability to resist water, vacuum and adapt to a wide temperature range, while the overall performance and stability of the battery are improved.
[0055] Comprehensive effect:
[0056] Technical problems solved: The above-mentioned preparation method effectively solved the technical problems of weak stress resistance of fiber electrodes, surface shear deformation fracture and difficulty in preparing fabric power sources.
[0057] Achieved multifunctionality: The constructed fabric devices not only have good mechanical strength and stability, but can also work normally under water immersion, high vacuum and wide temperature range environments, meeting the needs of various application scenarios.
[0058] Example 1
[0059] Step 1: Use acetone, water and dimethylformamide to ultrasonically clean the manganese dioxide powder, titanium wire and copper wire for 1 hour, then use deionized water to ultrasonically clean them 3 times, each washing time is 20 minutes, and then put them into a blast drying oven at 80°C to dry for 24 hours for use.
[0060] Step 2: Take 5g of manganese dioxide powder and add it to an agate ball mill, put in 2g of agate ball milling beads with a radius of 1mm, then put in 8g of agate ball milling beads with a radius of 8mm, add 4g of pure water, and ball mill for 7h. Pour all the slurry in the ball mill into a suction filtration device, put it into a blast drying oven after suction filtration, dry it at 50°C for 24h, then use a mortar to grind it into powder and evenly spread it in a porcelain ark, put it into a tube furnace at 250°C, anneal it for 2h, and collect it for use after natural cooling.
[0061] Step 3: Take 2.5g of N-methylpyrrolidone, add 0.1g of polyvinylidene fluoride, 0.2g of Mxene fiber and graphite, and 0.7g of the powder prepared in step 2, stir for 24h until the slurry is uniform, and add it to the slurry pool. Pass the current collector through the bottom of the slurry pool, the electrode drying box, fix it on the electrode collector, turn on the electrode drying box, heat it to 220°C, and then collect the electrode at a speed of 3cm / min for standby use.
[0062] The negative electrode components include: Zn-Cu alloy, etc. 90%; adhesive 5%; conductive agent 5%; the fiber negative electrode is prepared by the same process for standby use.
[0063] Step 4: Cut the PP-PE composite diaphragm into long strips and continuously and evenly wind them on the positive and negative electrodes prepared in step 3. The winding angle between the diaphragm and the positive electrode layer of the fiber battery is 10°, the winding speed is 300r / min, and the positive and negative electrodes wrapped with the diaphragm are spirally wound at a winding angle of 80°.
[0064] Step 5: Add 28.75 g zinc sulfate heptahydrate and 4.225 g hydrated manganese sulfate to 30 ml of deionized water and stir evenly. Transfer the solution to a 50 ml volumetric flask, then add deionized water to make up to 50 ml. Soak the positive and negative electrodes wound in step 4 in the electrolyte for 30 min.
[0065] Step 6: Take 10g of polyvinyl alcohol (PVA) powder, slowly add it to a mixed solution of 40g of dimethylformamide and acetone, stir for 24h until the powder is completely dissolved, and add the obtained solution to the slurry pool. Pass the battery wrapped in step 5 through the bottom of the slurry pool, heat it to 60°C in a drying oven, and then collect the battery at a speed of 160cm / min to complete the preparation of a high temperature resistant battery that can withstand continuous use on a commercial loom.
[0066] Example 2
[0067] Step 1: Use anhydrous ethanol, water and dimethylformamide to ultrasonically clean the vanadium oxide powder, iron wire and copper wire for 0.5 h, then use deionized water to ultrasonically clean them 3 times, each washing time is 40 min, and then put them into a 120° C. forced air drying oven to dry for 12 h for use.
[0068] Step 2: Take 5g of vanadium oxide powder and add it to an agate ball mill, put in 3g of agate ball milling beads with a radius of 2mm, then put in 10g of agate ball milling beads with a radius of 9mm, add 3g of pure water, and ball mill for 10h. Pour all the slurry in the ball mill into a suction filtration device, put it into a blast drying oven after suction filtration, dry it at 50°C for 10h, then use a mortar to grind it into powder and evenly spread it in a porcelain ark, put it into a tube furnace at 150°C, anneal it for 3h, and collect it for use after natural cooling.
[0069] Step 3: Take 2g of N-methylpyrrolidone, add 0.2g of polytetrafluoroethylene, 0.3g of graphite and 0.9g of the powder prepared in step 2, stir for 5h until the slurry is uniform, and add it to the slurry pool. Pass the current collector through the bottom of the slurry pool, the electrode drying box, and fix it on the electrode collector. Turn on the electrode drying box, preheat it to 140°C, and then collect the electrode at a speed of 120cm / min for standby use. The components of the negative electrode layer include: 95% Zn powder; 1.5% polytetrafluoroethylene as a binder; 3.5% graphite as a conductive agent. The same process is used to prepare a fiber negative electrode for standby use.
[0070] Step 4: Cut the PP-PE composite diaphragm into long strips and continuously and evenly wind them on the positive and negative electrodes prepared in step 3. The winding angle between the diaphragm and the positive electrode layer of the fiber battery is 170°, the winding speed is 200r / min, and the positive and negative electrodes wrapped with the diaphragm are spirally wound at a winding angle of 100°.
[0071] Step 5: Add 18.75 g zinc sulfate heptahydrate and 3.225 g hydrated manganese sulfate to 30 ml of deionized water and stir evenly. Transfer the solution to a 50 ml volumetric flask, then add deionized water to make up to 50 ml. Soak the positive and negative electrodes wound in step 4 in the electrolyte for 30 min.
[0072] Step 6: Take 10g each of polyvinyl butyral PVB and polyvinyl chloride PVC, slowly add them to a mixed solution of 50g dimethylformamide and ethanol, stir for 4h until the powder is completely dissolved, and add the obtained solution to the slurry pool. Pass the battery wrapped in step 5 through the bottom of the slurry pool, heat it to 220°C in a drying oven, and then collect the battery at a speed of 110cm / min to complete the preparation of the battery that can withstand continuous use on a commercial loom and is resistant to vacuum.
[0073] Example 3
[0074] Step 1: Use anhydrous ethanol, water and dimethylformamide to ultrasonically clean the manganate powder, titanium wire and copper wire for 1 hour, then use deionized water to ultrasonically clean them 3 times, each washing time is 50 minutes, and then put them into a 140°C forced air drying oven to dry for 2 hours for use.
[0075] Step 2: Take 5g of manganate powder and add it to an agate ball mill, put in 3g of agate ball milling beads with a radius of 2mm, then put in 10g of agate ball milling beads with a radius of 9mm, add 3g of pure water, and ball mill for 10h. Pour all the slurry in the ball mill into a suction filtration device, put it into a blast drying oven after suction filtration, dry it at 70°C for 5h, then use a mortar to grind it into powder and evenly spread it in a porcelain ark, put it into a tube furnace at 180°C, anneal it for 5h, and collect it for use after natural cooling.
[0076] Step 3: Take 2g of N-methylpyrrolidone, add 0.025g of polyvinylidene fluoride, 0.025g of graphite and 0.95g of the powder prepared in step 2, stir for 2h until the slurry is uniform, and add it to the slurry pool. Pass the current collector through the bottom of the slurry pool, the electrode drying box, and fix it on the electrode collector. Turn on the electrode drying box, preheat it to 170°C, and then collect the electrode at a speed of 160cm / min for standby use. The components of the negative electrode layer include: 99% Zn powder; 0.5% polytetrafluoroethylene as a binder; 0.5% graphite as a conductive agent. The same process is used to prepare a fiber negative electrode for standby use.
[0077] Step 4: Cut the PP, cable paper and cellulose diaphragm into long strips, and continuously and evenly wind them on the positive and negative electrodes prepared in step 3. The winding angle between the diaphragm and the positive electrode layer of the fiber battery is 75°, the winding speed is 260r / min, and the positive and negative electrodes wrapped with the diaphragm are spirally wound with a winding angle of 80°.
[0078] Step 5: Add 18.75 g zinc sulfate heptahydrate and 3.225 g hydrated manganese sulfate to 30 ml of deionized water and stir evenly. Transfer the solution to a 50 ml volumetric flask, then add deionized water to make up to 50 ml. Soak the positive and negative electrodes wound in step 4 in the electrolyte for 60 min.
[0079] Step 6: Take 10g of polyvinyl chloride (PVC), slowly add it to a mixed solution of 20g of dimethylformamide and ethanol, stir for 2h until the powder is completely dissolved, and add the obtained solution to the slurry pool. Pass the battery wrapped in step 5 through the bottom of the slurry pool, heat it to 110°C in a drying oven, and then collect the battery at a speed of 160cm / min to complete the preparation of the battery.
[0080] Step 7: Put the constructed fiber battery and wool together as the weft into the loom to weave the energy storage fabric.
[0081] A textile battery that can be used continuously and withstand high temperatures directly on a commercial loom has been realized.
[0082] Example 4
[0083] Step 1: Use acetone, water and dimethylformamide to ultrasonically clean the vanadium oxide powder, carbon fiber wire and copper wire for 2 hours, then use deionized water to ultrasonically clean them 3 times, each washing time is 80 minutes, and then put them into a 110°C forced air drying oven to dry for 4 hours for use.
[0084] Step 2: Take 5g of vanadium oxide powder and add it to an agate ball mill, put in 3g of agate ball milling beads with a radius of 2mm, then put in 10g of agate ball milling beads with a radius of 9mm, add 3g of pure water, and ball mill for 10h. Pour all the slurry in the ball mill into a suction filtration device, put it into a blast drying oven after suction filtration, dry it at a temperature of 110°C for 7h, then use a mortar to grind it into powder and evenly spread it in a porcelain ark, put it into a tube furnace at 290°C, anneal it for 4h, and collect it for use after natural cooling.
[0085] Step 3, take 3g of acetone and ethanol, add 0.025g of polyvinylidene chloride PVDC, 0.025g of carbon nanotubes and 0.95g of the powder prepared in step 2, stir for 2h until the slurry is uniform, and add it to the slurry pool. Pass the current collector through the bottom of the slurry pool, the electrode drying box, fix it on the electrode collector, turn on the electrode drying box, preheat it to 180℃, and then collect the electrode at a speed of 130cm / min for standby use. The components of the negative electrode layer include: 99% Zn powder; 0.5% polytetrafluoroethylene as a binder; 0.5% graphite as a conductive agent. The same process is used to prepare a fiber negative electrode for standby use.
[0086] Step 4: Cut the cable paper and cellulose diaphragm into long strips, and continuously and evenly wind them on the positive and negative electrodes prepared in step 3. The winding angle between the diaphragm and the positive electrode layer of the fiber battery is 95°, the winding speed is 220r / min, and the positive and negative electrodes wrapped with the diaphragm are spirally wound with a winding angle of 20°.
[0087] Step 5: Add 18.75g zinc sulfate heptahydrate and 3.225g hydrated manganese sulfate and 5% chitosan additive to 30ml deionized water and stir evenly. Transfer the solution to a 50ml volumetric flask, then add deionized water to 50ml. Soak the positive and negative electrodes wound in step 4 in the electrolyte for 120min.
[0088] Step 6: Take 8g of polyvinylidene chloride (PVDC), slowly add it to a mixed solution of 12g of dimethylformamide and acetone, stir for 3h until the powder is completely dissolved, and add the obtained solution to the slurry pool. Pass the battery wrapped in step 5 through the bottom of the slurry pool, heat it to 130°C in a drying oven, and then collect the battery at a speed of 280cm / min to complete the preparation of the battery.
[0089] Step 7: Put the constructed fiber battery into the loom as both the weft and the warp to weave the energy storage fabric. This realizes a fabric battery that can be used directly on a commercial loom and is vacuum-resistant and has a wide temperature range.
[0090] In summary, the present invention enhances the mechanical strength, electrochemical properties and environmental adaptability of fiber electrodes and fabric devices layer by layer through in-situ construction, interface matching and layer-by-layer composite preparation methods, thereby solving the technical problems of weak stress resistance of fiber electrodes and fracture due to surface shear deformation, and realizes the water resistance, vacuum resistance and wide temperature range effects of fabric devices, providing an effective solution for the preparation and application of fabric power sources.
Claims
1. A high vacuum, wide temperature range applicable fabric battery, characterized in that: The fabric battery is composed of a positive electrode composed of a current collector loaded with positive electrode active material, a separator layer, a negative electrode composed of a fiber negative electrode, and a surface packaging. The positive electrode active material is one of manganese dioxide, vanadium oxide or manganate or a mixture thereof, the proportion of the mixture is in the range of 70%-95%, the proportion of the adhesive is in the range of 1%-10%, and the proportion of the conductive agent is in the range of 1%-20%.
2. A high vacuum, wide temperature range applicable fabric battery according to claim 1, characterized in that: The fiber negative electrode components include 70%-100% of one of Zn or Zn-Cu alloy or a mixture thereof, 10%-0% of a binder, and 20%-0% of a conductive agent.
3. The high vacuum, wide temperature range applicable fabric battery according to claim 1, characterized in that: The current collector is a carbon-based or metal-based composite with a diameter of 20 μm-500 μm; The carbon-based material includes one or more of Mxene fiber, graphene fiber, and carbon fiber; The metal base includes one or more of copper wire, stainless steel wire, aluminum wire and titanium wire; The conductive agent includes one or more of acetylene black, carbon nanotubes, Super P, and graphite.
4. The high vacuum, wide temperature range applicable fabric battery according to claim 1, characterized in that: The surface packaging is a wrapping film, and the material of the film includes one or more of polyvinyl alcohol PVA, polyvinyl butyral PVB, polyvinyl chloride PVC, polyethylene PE and polyvinylidene chloride PVDC.
5. The high vacuum, wide temperature range applicable fabric battery according to claim 1, characterized in that: The adhesive is one or more of polytetrafluoroethylene, polyvinylidene fluoride, styrene-butadiene rubber and acrylonitrile multi-polymer.
6. A continuous preparation method for a high vacuum, wide temperature range applicable textile battery according to any one of claims 1 to 5, the specific steps are as follows: In-situ construction: The positive electrode active material slurry or the negative electrode active material slurry is evenly coated on the current collector, and then dried and solidified in an oven, and collected after roller pressing; Interface matching: A separator is selected and spirally wound on an electrode loaded with an active material, and the electrode wound with the separator is spirally wound with another fiber electrode to form a battery cell; Layer by layer compounding: After the battery cell is completely soaked with electrolyte, it is wrapped with polymer solution and dried in an oven to complete the preparation of the fiber battery.
7. According to the continuous preparation method of a high vacuum and wide temperature range applicable textile battery according to claim 5, the viscosity of the positive electrode active material slurry should be controlled at 2000mPa·s-15000mPa·s; The slurry is coated on the current collector at a speed of 3 cm / min-160 cm / min, and the drying temperature is 50°C-220°C; The active material loading density of the obtained electrode is 30 mg / m3-680 mg / m3.
8. According to the continuous preparation method of a high vacuum and wide temperature range applicable fabric battery according to claim 5, the diaphragm is one or more of PP, PE, cable paper, cellulose diaphragm, and non-porous diaphragm; The diameter of the fiber negative electrode is 0.02mm-0.5mm; The winding angle between the negative electrode or the separator and the positive electrode is 10°-170°, and the winding speed is 5r / min-300r / min.
9. According to the continuous preparation method of a high vacuum, wide temperature range applicable textile battery as described in claim 5, one or more polymer powders of the polymer polyvinyl alcohol (PVA), polyvinyl butyral (PVB), polyvinyl chloride (PVC), polyethylene (PE) and polyvinyl chloride (PVDC) solutions used in the surface encapsulation are dissolved in one or more solvents selected from acetone, dimethyl sulfoxide, dimethylformamide and ethanol and stirred thoroughly to obtain the result.
10. A flexible battery fabric, characterized in that: The flexible battery fabric is woven and knitted by a high vacuum, wide temperature range applicable fabric battery as described in any one of claims 1-5.
Citation Information
Patent Citations
Linear flexible lithium ion battery and preparation method thereof
CN104617336A
Fiber-like-structured lithium ion battery and preparation method
CN107591559A
High-performance fiber-shaped Zn-Co aqueous battery capable of preventing water and preparation method thereof
CN108598601A
All-solid-state lithium-sulfur battery with cable structure, and preparation method thereof
CN111740170A
Solid-state lithium ion battery capable of heating cable structure, and preparation method and application thereof
CN114094236A